1974
DOI: 10.1071/ar9740105
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Eutypa armeniacae. II. Studies of the interaction between E. armeniacae and Fusarium lateritium, and their relative sensitivities to benzimidazole chemicals

Abstract: Fusarium lateritium, a saprophyte sometimes associated with apricot trees, inhibits in vitro germination and growth of Eutypa armeniacae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In our studies of antagonistic and mycoparasitic fungi, in Hungary, an isolate of Fusarium lateritium showed a similar inhibitory effect on different fungi to those described by CARTER and PRICE (1974). We mentioned that this fungus can parasite some phytopathogenic and saprophytic fungi.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…In our studies of antagonistic and mycoparasitic fungi, in Hungary, an isolate of Fusarium lateritium showed a similar inhibitory effect on different fungi to those described by CARTER and PRICE (1974). We mentioned that this fungus can parasite some phytopathogenic and saprophytic fungi.…”
supporting
confidence: 70%
“…Some isolates of Trichoderma: T. koningii (Tk-3) and T. pseudokoningii parasited hyphae of F. lateritium. The mutual inhibition of the growth of the colonies of F. lateritium and the test fungi can be explained by the production of fungistatic diffusible substances, as it was demonstrated by CARTER and PRICE (1974).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The iatrogenic effect of fungicides is due to the removal of these natural biological control mechanisms and the loss of natural biological control agents has been implicated in other iatrogenic disease situations as reviewed by Griffiths (1981). In at least one of these, dieback of apricots caused by Eutypa armeniaceae, the active component was identified and subsequently used in an integrated control programme (Carter and Price 1974). There is increasing evidence that endophytes may play a role in limiting disease and Arnold et al (2003) have recently shown that endophytes in cacao can protect against leaf infection by Phytophthora.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, management of Eutypa dieback relied on sanitary practices as well as the protection of the surface area of pruning woods by phytosanitary products (Carter and Price 1974;Rolshausen and Gubler 2005;Bester et al 2007). At the moment, apart from fungicide use, various Trichoderma strains are in discussion as potential biocontrol agents for dieback (John et al 2004;Halleen et al 2010;Kotze 2008).…”
Section: Biocontrol Of Fungal Trunk Diseasesmentioning
confidence: 99%